THE INACTIVATION OF HELMINTH EGGS WITH THE NARROW BANDWIDTH RADIATION OF EXCIMER LAMPS - E. I. Lipatov; E. A. Sosnin; S. M. Avdeev (Российский паразитологический журнал, 2016)
Objective of research: to study the inactivation of eggs of Opisthorchis felineus and Diphyllobothrium latum in the water by the narrowband ultraviolet excimer lamp radiation 222 and 282 nm depending on the surface radiation dose. Materials and methods: Helminth eggs were detected by the Kato technique. The revealed eggs were flushed into a plastic container with the distilled water and exposed to UV. The inactivation of eggs was confirmed by the method of optical microscopy. Results and discussion: It was found that the recovery of helminth eggs from water was 40-70% more efficient by using UV radiation at 222 nm than at 282 nm. In addition, the surface radiation dose at 222 nm (up to 5 mJ/cm2) was one order less than at 282 nm (up to 100 mJ/cm2). Up to 30 % of the initial amount of Opisthorchis felineus eggs were inactivated at 282 nm surface radiation dose (up to 100 mJ/cm2). Up to 85 % of the initial quantity of Opisthorchis felineus eggs were inactivated at 222 nm radiation on the water surface (up to 5 mJ/cm2). Up to 56 % of Diphyllobothrium latum eggs were inactivated at the comparable 222 nm surface radiation dose.  Due to the higher photon energy, the more intensive shortwave radiation at 222 nm breaks shells of Opisthorchis felineus eggs more effectively. We have a reason to suppose that some features of Diphyllobothrium latum egg shells make its inactivation at 222 nm less efficient in comparison with the inactivation of Opisthorchis felineus eggs at the same wavelength of radiation.